Across Archival Limits: Colonial Records, Changing Ethnonyms, and Geographies of Knowledge. - Erbig Jr., Jeffrey A.; Latini, Sergio (Ethnohistory, 2019)
This article examines relationships between archival records produced in borderland spaces and the histories of autonomous (non-subjugated and non-missionized) Indigenous peoples. Focusing on the Banda Oriental region of Southeastern South America, it argues that the geographical content, dispersion, and curation of colonial records have served to silence Native pasts. As Portuguese, Spanish, and Jesuit administrators sought possession of this borderland, they overstated the reach of their own settlements and strategically ascribed ethnic labels to Indigenous neighbors to appropriate their lands or delegitimize their sovereignty. The geographical dispersion of colonial records over time has masked the inconsistencies of such claims, and colonial ethnogeographic imaginations thus persist. By reading colonial sources from multiple settlements against one another, this article identifies contradictions in the geographic and ethnographic information they provide, laying a foundation for new ethnogeographic imaginations that center the spaces and agency of autonomous Indigenous communities.